How the COVID-19 Pandemic has Changed the Game of Soccer - Link, Daniel; Anzer, Gabriel (International Journal of Sports Medicine, 2021)
This study explores the influence of corona-specific training and playing conditions - especially empty stadiums - on match performance, contact behavior, and home advantage in the Bundesliga (BL) and Bundesliga 2 (BL2). We analyzed the 2017/18, 2018/19, and 2019/20 seasons and compared matches in rounds 26–34 before shutdown with “ghost” matches after restart. Results show increased running activity for high intensity distance: (+ 6.1%) and total distance covered (+ 4.3%). In BL2 in particular there were also changes in tactical aspects of the game (time in last third: –6.3%, pressure on pass receiver: –8.6%, success of attacking duels: –7.9%, share of long passes completed: + 15.6%, outplayed opponents per pass: –14.7%). Contact time to other players (< 2 m distance) was 15:35 mins per match. After restart, contact was reduced, especially when the ball was not in the last third (–11.2%). Away wins increased by +44.2% in BL and the home-away difference in yellow cards changed in favor of the away team (+31.2%) in BL2. We conclude that empty stadiums have reduced home advantage and decreased referee bias when awarding yellow cards. Player behavior might have been affected by tactical demands and/or conscious or unconscious self-protection.
Keywords: COVID-19; sport analytics; performance analysis; match performance; home advantage; contact time; referee bias